Innovation Management in Cultural Heritage Tourism: Experience from the Amphawa Waterfront Community, Thailand - Malinvisa Sakdiyakorn (2018)
© 2015 Asia Pacific Tourism Association. This paper examines how innovation management could bring greater opportunities for cultural heritage tourism at the community level. A two-stage investigation using in-depth, semi-structured interviews with key informants and random, on-site, short, structured interviews with tourists was conducted to uncover the preconditions and categories of innovation that support cultural heritage tourism in the Amphawa Waterfront Community, a renowned tourist destination in Thailand. The results from the study suggest that the “willingness” and “capability” of those involved in a community-based cultural heritage initiative are key to fostering a multitude of innovations but may not guarantee its long-term success. A mind-set towards sustainability that considers economically, socially, and environmentally viable innovations is required for sustainable growth. A call for innovation management from this sustainable angle is proposed at the end.